If p3 - q3 = (p - q){(p -q)2 + xpq}, then the value of x is?

  • 11
  • 2-1
  • 33
  • 42
Answer:- 1
Explanation:-

Solution:
p3q3=(pq){(pq)2+xpq}(pq){p2+q2+pq}=(pq){p2+q22pq+xpq}p2+q2+pq=p2+q22pq+xpq3pq=xpqx=3

Post your Comments

Your comments will be displayed only after manual approval.

", "dateCreated": "7/24/2019 10:09:12 AM", "author": { "@type": "Person", "name": "Nitin Sir" } }, "suggestedAnswer": { "@type": "Answer", "text": "
Solution:
p3q3=(pq){(pq)2+xpq}(pq){p2+q2+pq}=(pq){p2+q22pq+xpq}p2+q2+pq=p2+q22pq+xpq3pq=xpqx=3
", "dateCreated": "7/24/2019 10:09:12 AM" } }
Test
Classes
E-Book